Lessons learned during the COVID-19 pandemic: a single institution radiology chief resident experience - Roytman, Michelle (Clin Imaging, 2020)
Coronavirus Disease 2019 (COVID-19) has posed incredible new challenges for radiology residency programs, including resident training under tenuous and uncertain conditions, barriers to communication, deployment-induced anxiety, and social isolation. Chief residents and program leadership play a critical role in guiding radiology residents through these unprecedented times. Best practices and creative approaches experienced in a single institution's residency program located in New York City are shared in an effort to encourage other programs struggling with similar obstacles to prioritize resident education and wellness.